A percepção de farmacêuticos na implantação do Cuidado Farmacêutico na Atenção Básica em uma região do município de São Paulo - D’Andréa, Renato Dias [UNIFESP] (2019)
The Pharmaceutical Care constitutes the integrated action of the pharmacist for the promotion, the protection, the health recovery and the prevention of diseases. It aims to the education in the health field and to the promotion of a rational use of drugs through the pharmaceutical clinical services and through the pedagogical-technical activities directed to the individual, the family, the community, and the health team. Objective: Describing the perception of the Primary Care pharmacists who participated in the process of pharmaceutical care implementation in a region of the township of São Paulo. Method: A qualitative research with a descriptive approach. The data collection was carried out with ten pharmacists who participated in two focus groups in May and August 2018 (CEP UNIFESP 2.480.641/ CEP SMS 2.587.651). The data were submitted to the Bardin’s Content Analysis. Results: Starting from 52 record units and 10 categories, 3 syntheses about the process of pharmaceutical care implementation were realized: Synthesis 1- The positive aspects and the facilitators highlighted by the pharmacists concerned the care practice, such as the consultation and the listening time, looking beyond the pharmacotherapy and the specific instruments; the insertion in the Basic Health Unit (BHU); the formation and the training; the expansion of the scope of activities such as household visits and educational groups. These aspects responded to the pharmacists’ expectations, besides responding to the managers’ support and to the demand for the implementation of goals, flows and protocols to optimize the pharmaceutical care; Synthesis 2- The negative aspects and the barriers highlighted by the pharmacists intertwine when related to the sensations and feelings about the execution capability of the service; the demand for goals and the lack of support in the management; Synthesis 3- The Primary Care pharmacists highlighted the influence of the user in the implementation of the pharmaceutical care; the team role in the execution of the project with moments of recognition and strangeness; the profile and the skills required for the pharmacist, such as the pro-activity, empathy, and auto-valorization extended the concept of Pharmaceutical Care, besides the prescription, so differentiating it from the Pharmaceutical Care. Conclusion: With the results obtained, it was possible to describe the perception of the pharmacists in the Pharmaceutical Care implementation through the positive and negative aspects and through the necessary advances reported by the pharmacists. Thus, all the actors involved in this practice – the users, the health team, the managers, and the pharmacists - are expected to recognize their role and to value new forms of care in the National Health System.